AB073. Clinical analysis of primary Penoscrotal extra-mammary Paget’s disease: a report of 22 cases - Bao, Zhengqing (Transl Androl Urol, 2016)
OBJECTIVE: To investigate the clinical characteristics, treatment and prognosis of primary Penoscrotal extra-mammary Paget’s disease (PSPD). METHODS: The clinical and pathological data of 22 cases of primary PSPD were retrospectively reviewed. Overall survival rate was analyzed with Kaplan-Meier survival curve method. RESULT: The median age of onset was 64.5 (range, 39–84) years. Erythema, itchiness, ulcerate, exudation and pain were the major manifestations. All patients were treated with wide surgical excision. The rate of invasive patients was 77.3%. Twelve patients exhibited local recurrence or/and metastases, and significant differences existed in the status of surgical margins and the depth of invasion (P=0.015, P=0.01). Inguinal lymph nodes were generally involved. The difference of the delay of diagnosis between metastasis and non-metastasis was significant (P=0.04). 5-year survival rate of overall and invasive patients were 33.7% and 27.9% respectively. CONCLUSIONS: Primary PSPD, with the characteristic of long duration, high invasive tendency and high incidence of local recurrence or metastases, generally occurs in the elderly. Surgery should be performed at first. The delay of diagnosis, positive surgical margins and inguinal lymph node involved are important risk factors. Biopsy, frozen section and inguinal lymph node biopsy (ILNB) can promote prognosis.